2020
DOI: 10.21608/eajbsf.2020.84488
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical and Biological Anti-mycotoxins on Performance, Haematological, Biochemical and Immunological Parameters of Broiler Chickens during Aflatoxicosis

Abstract: The journal of Toxicology and pest control is one of the series issued twice by the Egyptian Academic Journal of Biological Sciences, and is devoted to publication of original papers related to the interaction between insects and their environment. The goal of the journal is to advance the scientific understanding of mechanisms of toxicity. Emphasis will be placed on toxic effects observed at relevant exposures, which have direct impact on safety evaluation and risk assessment. The journal therefore welcomes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 76 publications
3
5
0
Order By: Relevance
“…There was also a shortage of platelets in all treatments compared to the control, while platelets increased after treatments. These results are in agreement with those by Kilany et al [34] and Tarabees et al [35]. The histological examinations of the colon and spleen demonstrated that the Piroxicam drug had a severe effect on them.…”
Section: Discussionsupporting
confidence: 93%
“…There was also a shortage of platelets in all treatments compared to the control, while platelets increased after treatments. These results are in agreement with those by Kilany et al [34] and Tarabees et al [35]. The histological examinations of the colon and spleen demonstrated that the Piroxicam drug had a severe effect on them.…”
Section: Discussionsupporting
confidence: 93%
“…Hepatic sections from broiler group after receiving Synertox ® showed fibrous tissue proliferation infiltrated with mixed leukocytes and few leukocytic cells infiltration around central vein. These findings were in the line with kilany et al (38) who reported that liver treated with product similar to Synertox ® showed portal and interstitial leucocytic aggregation in hepatic cells.…”
Section: Efficacy Of T-nil Plus® and Synertox® On Chickensupporting
confidence: 91%
“…Renal sections from broiler group after receiving Synertox ® showed congested interstitial blood vessels and mild interstitial edema. These results were relatively similar to those of kilany et al (38) who reported that kidney treated with product similar to Synertox ® showed acute cell swelling of renal tubules and congestion. Duodenal sections from broiler treated groups (G2, G3) showed desquamated villous epithelium due to the increase in lymphocyte populations due to the anti-inflammatory role of the tested agents in the duodenum, these results were in accordance with those of Awadin et al (73)…”
Section: Efficacy Of T-nil Plus® and Synertox® On Chickensupporting
confidence: 91%
“…The elevated serum level of creatinine in this investigation demonstrated aflatoxin's nephrotoxicity. An early sign of aflatoxicosis was this rise in creatinine levels (Kilany et al, 2020). HSCAS and SC substantively (p<0.05) improved serum biochemical items, signifying that they were successful in warding off AFB1 by inhibiting its adverse influence by raising serum conesituents (Attia et al, 2013;.…”
Section: Discussionmentioning
confidence: 88%